The game as a didactic strategy in teacher training in ICT and disability (European Journal of Child Development, Education and Psychopathology, 2019)
In recent years, considerable progress has been made in analyzing ICTs as significant instruments that favor the inclusion of people with different types of cognitive, sensory, or motor diversity. Although there are quality practices linked to the use of ICT and an increasing interest in the educational use of these technological tools, there is still a great concern to solve the different difficulties in digital competence that teachers present, and even more in contexts of diversity. Therefore, teachers are configured as a key element to achieve full inclusion of ICT in the classroom. To carry out a diagnosis in relation to the training and knowledge of Primary School teachers, in active employment, in relation to ICT applied to people with functional diversity. Qualitative research design, developed from the Grounded Theory approach. The information has been obtained from the analysis of 52 interviews conducted with professionals in the education sector of the Spanish state (members of management teams, ICT coordinators, directors and technological advisors of training centers). It should be noted that the participants accurately recognize the benefits that these technological tools bring to students with functional diversity and play as a teaching tool. The low training of teachers to apply ICT to people with disabilities stands out. The game is presented as a first order strategy for the application of ICT to students with disabilities.